2018
DOI: 10.1029/2018ja025822
|View full text |Cite
|
Sign up to set email alerts
|

First Observations of Recurring HF‐Enhanced Topside Ion Line Spectra Near the Fourth Gyroharmonic

Abstract: We present first incoherent scatter radar observations of systematically recurring, high-frequency (HF)-enhanced ion line spectra at the topside F-region ionosphere, during magnetic field aligned HF pumping in an O-mode polarization. The European Incoherent Scatter UHF radar was directed in magnetic zenith on 9-11 March 2016 while stepping the pump frequency across the double resonance of the fourth harmonic of the electron gyrofrequency and the local upper hybrid frequency, in a 3-min-on, 3-min-off pump cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 55 publications
7
14
0
Order By: Relevance
“…We present observations of two separate cases of topside HF-enhanced ion lines (THFIL). THFIL simultaneous to bottomside HFIL (BHFIL), and conditioned by the relative proximity of the HF pump frequency to the bottomside double resonance frequency, consistent with previous observations (Rexer et al, 2018) were observed for HF pulses on 19th October. Recurring THFIL appearing after BHFIL have faded and conditioned by the relative proximity to the double resonance frequency on the topside ionosphere, were observed on 18th October.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…We present observations of two separate cases of topside HF-enhanced ion lines (THFIL). THFIL simultaneous to bottomside HFIL (BHFIL), and conditioned by the relative proximity of the HF pump frequency to the bottomside double resonance frequency, consistent with previous observations (Rexer et al, 2018) were observed for HF pulses on 19th October. Recurring THFIL appearing after BHFIL have faded and conditioned by the relative proximity to the double resonance frequency on the topside ionosphere, were observed on 18th October.…”
supporting
confidence: 88%
“…The first consistently recurring topside HF enhanced ion line (THFIL) spectra and their relation to pump frequencies close to the 4th gyroharmonic frequency were shown by Rexer et al (2018). Observations of THFIL from an experiment in 2013 were also reported by Borisova et al (2020).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Evidence of L-mode propagation of the EISCAT Heating beam has previously been obtained as transionospheric propagation for f 0 < f oF 2 < f 0 +f e /2, in which case an Lmode wave would not be reflected but pass through the ionospheric plasma density peak. This was observed by direct measurement on the CASSIOPE spacecraft (Leyser et al, 2018) and indirectly by EISCAT UHF radar observations of ion acoustic lines in the topside ionosphere (Rexer et al, 2018). Figure 6 also displays the altitude of the plasma resonance (white lines in Fig.…”
Section: Discussionmentioning
confidence: 63%
“…These results are consistent with the pump wave propagating in the L mode in magnetic zenith and in the O mode at angles deviating from the zenith direction. Evidence of L-mode propagation of the EISCAT Heating beam has previously been obtained as transionospheric propagation for f 0 < f oF 2 < f 0 + f e /2, in which case an L-mode wave would not be reflected but pass through the ionospheric plasma density peak, by direct measurement on the CASSIOPE spacecraft (Leyser et al, 2018) and indirectly by EISCAT UHF radar observations of ion acoustic lines in the topside ionosphere (Rexer et al, 2018). Figure 6 also displays the altitude of the plasma resonance (white line in the right panels).…”
Section: Discussionmentioning
confidence: 98%